Evidencing the effectiveness of upper limb prostheses: a multi-stakeholder perspective on study requirements - Jones, Hannah; Chadwell, Alix; Dyson, Matthew (Frontiers in Health Services, 2023)
The provision of upper limb prosthetic devices through the National Health Services (NHS) within the United Kingdom is driven by national policies. NHS England have recently published a new policy to provide multi-grip myoelectric hands. The policy highlighted that there was limited evidence to support its deployment and it will be reviewed should new information arise. The clear identification of the evidence gap provides an opportunity for the academic research community to conduct studies that will inform future iterations of this and other upper limb prosthetic related policies. This paper presents a summary of findings and recommendations based on two multi-stakeholder workshops held in June 2022 and July 2022, which explored the design requirements for policy-driven research studies. The workshops involved people from a broad range of stakeholder groups: policy, academia, NHS clinical and management, industry, and a person with upper limb absence. The workshop discussions focused on the research questions that NHS England identified in the policy evidence review: (1) Clinical Effectiveness; (2) Cost Effectiveness; (3) Safety; and (4) Patient Subgroups. The recommendations based on stakeholder discussions included the need to gather qualitative and quantitative research evidence, use goal-based outcome measures, and conduct longitudinal studies. Future research studies also need to address the complexities of conducting national and international policy-driven research, such as clinical resource capacity and participant involvement.